Teacher’s Perceptions of STEM Education at the Primary Level in Morocco - Lechhab, Abdelhamid; Benqassou, Issam; El-Hars, Fouad; Chekour, Mohammed; Hafid, Moulay Mustapha (International Journal of Interactive Mobile Technologies (iJIM), 2023)
STEM education is critical in developing students' interest in science and technology. Primary schools establish the groundwork by teaching fundamental technology ideas. Digital programs are favored over old paper-based approaches in response to current demands. The essential objective of this research is to show how information and communication technology (ICT) can improve the quality of teaching, learning, and motivation among primary school students. A questionnaire has been sent to 80 teachers at elementary schools, and a quantitative methodology was utilized to examine their thoughts. As an evaluation instrument, an eight-question quiz has been utilized to assess the usefulness and significance of ICT in promoting active and autonomous learning, resulting in creating a student-centered education approach. According to the research, the majority of teachers support the use of ICT as an of use pedagogical tool that fosters a proactive learning culture in young learners.